الانزياح التركيبي بين النحو العربي القديم والدرس اللساني الحديث - الساكر, مسعودة; دجال, حفصية; عويسي, وهيبة (University of Eloued جامعة الوادي, 2024)
يهدف هذا الى ابراز تأصل ظاهرة الانزياح التركيبي في الحضارة اللغوية العربية، كظاهرة نحوية بلاغية، مع التركيز على استخلاص أوجه المفارقة والالتقاء بين دراسة هذه الظاهرة اللغوية بين النحو العربي القديم، والدرس اللساني الحديث، وخلص البحث الى تبيان مفهوم البنية العميقة حسب المدرسة التوليدية التحويلية، والتي لا تلتقي البتة مع مفهوم البنية العميقة في الدرس اللغوي العربي وخاصة عند تطبيقها على الدراسات القرآنية، نظرا لاختلاف مفهومها الجوهري بينهما؛ حيث فصلت الدراسات اللسانية المعنى على التركيب؛ لذلك وجب التنبيه الى أهمية القراءة الداخلية لقضايا التراث اللغوي العربي، وفق أدوات المعرفة اللغوية الراهنة؛ حيث نصنع للمعرفة اليوم امتدادا مع معارفنا التي أسستها حضاراتنا اللغوية، متى ما كان ذلك ممكنا. This aims to highlight the rootedness of the phenomenon of syntactic shift in the Arabic linguistic civilization, as a grammatical and rhetorical phenomenon, with a focus on extracting the aspects of paradox and convergence between the study of this linguistic phenomenon between ancient Arabic grammar and the modern linguistic lesson. The research concluded by clarifying the concept of deep structure according to the generative-transformative school. Which does not coincide at all with the concept of deep structure in the Arabic linguistic lesson, especially when applied to Quranic studies, due to the difference in its fundamental concept between them. Linguistic studies separated meaning from structure. Therefore, attention must be paid to the importance of internal reading of issues of the Arabic linguistic heritage, according to current linguistic knowledge tools. Today we make knowledge an extension of our knowledge established by our linguistic civilizations, whenever possible.
أفعال القلوب في سورة الكهف أنموذجا
415/006
Keywords: الانزياح التركيبي، النحو العربي القديم، الدرس اللساني الحديث، أفعال القلوب، سورة الكهف; Syntactic shift; ancient Arabic grammar; modern linguistic lesson; actions of hearts; Surah Al-Kahf